FANDOM HOBBY ENGAGEMENT AND EMPLOYEE WELL-BEING: THE MEDIATING ROLE OF WORK-LIFE BALANCE AMONG INDONESIAN MILLENNIAL WORKERS - Pramana Saputra; Endah Mayasari; Uray Ndaru Mustika; Rizani Ramadhan; Bintoro Bagus Purmono (MANAJEMEN DEWANTARA, 2026)
The growth of popular culture and the creative economy has transformed fandom related activities into part of the modern lifestyle among working adults. Activities such as collecting figures, assembling model kits, gaming, and participating in fandom communities are increasingly used by millennial employees as leisure activities and psychological recovery mechanisms from work related stress. This study aims to examine the effect of fandom hobby engagement on employee well-being through the mediating role of work-life balance among Indonesian millennial workers. This study employs a quantitative approach using a survey method. The population consists of millennial employees in Indonesia who actively engage in fandom related hobbies. Data were collected through an online questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results are expected to show that fandom hobby engagement positively influences work-life balance and employee well-being. In addition, work-life balance is predicted to mediate the relationship between fandom hobby engagement and employee well-being. This study contributes to the literature on employee well-being, occupational psychology, work-life balance, and fandom culture within the context of the creative economy